Resilience of Muslims Minority and Islamic Education in Cambodia - Junaidi, Junaidi (BiCED Proceeding, 2023)
This research aims to reveal how the resilience of Muslim minority communities and Islamic education in Cambodia. Through various stages of this study, literature sources were used as the main source of research data. Initially, look for information in books, journals, articles, and other papers that are relevant to the subject being discussed. Secondly, a content analysis approach is used to analyze the data. The outcomes demonstrated that the social capital that the Muslim community in Cambodia possesses includes a sense of identification with and attachment to others who share that identity. Related to Islamic education institutions in Cambodia, lacks standardized norms, especially in the aspects of curriculum, teaching staff, learning resources, and educational facilities. Cambodian Muslims are able to coexist with other religious communities in harmony and peace due to the support of the government and society. The relationship between the Cambodian Muslim community and the government is also harmonious. The Cambodian government also pays strong attention to the existence of Islamic Education. Based on the results of the research, it is concluded that the Cambodian Muslim community has been able to build social connections after the fall of the Polpot regime through social bonding, social bridging and social linking.